Ventral hernia with uterine rupture after vaginal delivery - Jung Mi Byun; Dae Hoon Jeong; Young Nam Kim; Chul Hoi Jeong; Kyung Bok Lee; Moon Su Sung; Ki Tae Kim (Elsevier, 2014)
Objective: Ventral hernia is uncommon during pregnancy and is extremely rare in postpartum women. It leads to a life-threatening emergency. Case report: A 33-year-old woman, gravida 2 para 1, was admitted to our institute with severe abdominal pain and overdistended abdomen immediately after a full-term vaginal delivery. She had a normal prenatal course and denied having any medical and surgical history. The primipara woman with no history of abdominal surgery was diagnosed with a ventral hernia with uterine rupture after vaginal delivery. We performed an emergency laparotomy and primary repair of the uterine rupture and abdominal wall defect. An abdominal binder was provided for the postoperative period. The patient's postoperative period was uncomplicated. She was discharged from the hospital after 12 days. Conclusion: If a patient has hernia-related symptoms or complications, the diagnosis and management of the hernia should be performed as soon as possible, regardless of the onset, to decrease maternal and fetal mortality.